(untitled) (人文学刊, 2025)
摘要 随着数字媒介生态的成熟与人工智能生成内容技术的突破性进展，动态视觉识别系统的设计范式正经历一场从静态到动态、从预设到生成的深刻变革。本研究旨在系统探讨AIGC背景下动态视觉识别系统的发展趋势与内在逻辑。论文首先界定了动态视觉系统的核心概念，并分析了技术、媒介、用户与商业四重驱动因素。进而，通过案例比较剖析了AIGC如何重塑其构建模式、催生新美学范式，并引发系统一致性的新挑战。在此基础上，论文前瞻性地提出四大核心趋势：数据驱动的个性化动态系统、高度融合的交互与沉浸体验、人机协同中设计师角色的进化，以及在信息过载背景下“返璞归真”的价值回归。最后，本文对AIGC可能引发的美学同质化、设计伦理及技术依赖等挑战进行了批判性反思。研究表明，未来的动态视觉识别系统将超越固定的视觉规范，演进为一个智能的、可生长的“视觉有机体”，而设计师的核心价值将回归于战略洞察、叙事构建与人文关怀。 Abstract With the maturation of the digital media ecosystem and the breakthrough advancements in Artificial Intelligence Generated Content (AIGC) technology, the design paradigm of dynamic visual identity systems is undergoing a profound transformation—shifting from static to dynamic, and from pre-set to generative. This study aims to systematically explore the development trends and inherent logic of dynamic visual identity systems within the context of AIGC. The paper begins by defining the core concepts of dynamic visual systems and analyzing the quadruple driving factors: technology, media, user needs, and commercial competition. Furthermore, it examines how AIGC is reshaping construction modes, catalyzing new aesthetic paradigms, and introducing new challenges to systemic consistency through comparative case studies. On this basis, the paper prospectively identifies four core trends: data-driven personalized dynamic systems, highly integrated interactive and immersive experiences, the evolution of the designer’s role in human-machine collaboration, and the value return to "simplicity and authenticity" against the backdrop of information overload. Finally, a critical reflection is conducted on the challenges posed by AIGC, including aesthetic homogenization, design ethics, and over-reliance on technology. The research demonstrates that the future dynamic visual identity system will transcend fixed visual specifications, evolving into an intelligent, growing "visual organism," while the core value of designers will revert to strategic insight, narrative construction, and humanistic care.